Jewish medical resistance in the Holocaust - Grodin, Michael A. 1951- HerausgeberIn (Berghahn Books, 2014)
"Faced with infectious diseases, starvation, lack of medicines, lack of clean water, and safe sewage, Jewish physicians practiced medicine under severe conditions in the ghettos and concentration camps of the Holocaust. Despite the odds against them, physicians managed to supply public health education, enforce hygiene protocols, inspect buildings and latrines, enact quarantine, and perform triage. Many gave their lives to help fellow prisoners. Based on archival materials and featuring memoirs of Holocaust survivors, this volume offers a rich array of both tragic and inspiring studies of the sanctification of life as practiced by Jewish medical professionals. More than simply a medical story, these histories represent the finest exemplification of a humanist moral imperative during a dark hour of recent history."